Effect of ethanol extract of leaf of Cajanus indicus spreng in carbon tetrachloride induced hepatopathy in rates in relation to free radical scavenging action (Journal of Nobel Medical College, 2012)
Phytochemicals, that is, chemicals present in various plants and herbs , are now becoming important candidates for development of drugs.Wide range of medicinals plants {Plants from which potential photochemicals are isolated for development of drugs for treatment of diseases}present in South Asian countries have now been increasingly utilized for development of phytomedicines. Treatment with ethanol extract of leaf of Cajanus indicus Spreng at a dose of 50 mg /kg body weight for 20 days, after induction of hepatotoxic damage by CCl4, produce significant elevation of the hepatic injury. The liver marker enzymes like(Aspartate Transaminate) AST, GGT(Gamma Glutamyl Transferase), ALT(Alanine Transaminase) and ALP(Alkaline Phosphatase) decreased significantly at the above dose showing the optimum effect against hepatic damage. The liver antioxidant enzymes SOD, catalase, glutathione peroxidase, glutathione reductase and glutathione transferase and the membrane damaging indicators TBARS(Thiobarbituric Acis Reactive Species), conjugate diene and marker of glutathione status indicate the mechanism of healing action to be due to scavenging of free radicals or ROS. The results thus gives a confirmatory proof that the healing action of ethanol extract of leaf of Cajanus indicus Spreng is for shifting of equilibrium from the peroxidant to antioxidant side and the leaf acts as a natural antioxidant and healer of CCl4 induced hepatotoxicity.DOI: http://dx.doi.org/10.3126/jonmc.v1i1.7284 Journal of Nobel Medical College Vol.1(1) 2011 20-26